A proposed model to study immunologic changes during chronic rhinosinusitis exacerbations: data from a pilot study - Rank, Matthew A; Hagan, John B; Samant, Shefali A; Kita, Hirohito (American journal of rhinology & allergy, 2013)
One way to gain insight into the pathophysiology of chronic rhinosinusitis (CRS) is to study the immunologic changes that occur with exacerbation. This study describes the immunologic changes during CRS exacerbation We performed a prospective study to investigate the immunologic changes seen during exacerbation of CRS with nasal polyposis. We recruited adult subjects who met clinical criteria for CRS with sinus CT scan within the past 5 years with Lund-Mackay score of >5 and nasal polyps. Subjects underwent a baseline visit with collection of nasal secretion and nasal wash. With acute worsening of symptoms, subjects underwent 6 near-consecutive-day collections and one follow-up collection 2 weeks later. IL-6, IL-33, eosinophil major basic protein (MBP), eosinophil-derived neurotoxin (EDN), myeloperoxidase (MPO), and uric acid were measured on the nasal samples from each visit. A total of 10 subjects were recruited and 9 had acute worsening of CRS during the study period. Eight of the nine subjects were women and ages ranged from 26 to 56 years. At baseline, most inflammatory parameters were low and eight of the nine subjects were on intranasal corticosteroids. Compared with baseline measurements, IL-6, MBP, MPO, EDN, and uric acid were significantly elevated during CRS exacerbation. Levels of IL-6 and MBP (r = 0.47) levels as well as IL-6 and MPO (r = 0.75) were both significantly correlated (p < 0.01). Prospective study of CRS exacerbations is feasible and provides insights into the immunologic mechanisms of CRS.